2023
DOI: 10.1021/acsami.3c07687
|View full text |Cite
|
Sign up to set email alerts
|

Bioderived Laser-Induced Graphene for Sensors and Supercapacitors

Anna Chiara Bressi,
Alexander Dallinger,
Yulia Steksova
et al.

Abstract: The maskless and chemical-free conversion and patterning of synthetic polymer precursors into laser-induced graphene (LIG) via laser-induced pyrolysis is a relatively new but growing field. Bioderived precursors from lignocellulosic materials can also be converted to LIG, opening a path to sustainable and environmentally friendly applications. This review is designed as a starting point for researchers who are not familiar with LIG and/or who wish to switch to sustainable bioderived precursors for their applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 197 publications
(567 reference statements)
0
7
0
Order By: Relevance
“…These preparation methods have complex processes, take a long time, have high costs, and are prone to secondary contamination, causing environmental pollution and other problems. 111 Laser treatment 112,113 and sunlight 114 are the most commonly used green methods for reducing graphene oxide, but they have not been widely used in industry because their technology is still immature and in the laboratory stage. Plasma technology has attracted research interest from scholars because of its high efficiency and pollution-free characteristics and because it can be used in combination with traditional methods.…”
Section: Graphenementioning
confidence: 99%
“…These preparation methods have complex processes, take a long time, have high costs, and are prone to secondary contamination, causing environmental pollution and other problems. 111 Laser treatment 112,113 and sunlight 114 are the most commonly used green methods for reducing graphene oxide, but they have not been widely used in industry because their technology is still immature and in the laboratory stage. Plasma technology has attracted research interest from scholars because of its high efficiency and pollution-free characteristics and because it can be used in combination with traditional methods.…”
Section: Graphenementioning
confidence: 99%
“…It can be considered as a rapid, pattering strategy, in which both production and patterning are carried out simultaneously, as compared to other graphene synthesis methodologies [2]. Its high electrical conductivity and high surface area have made LIG a promising electrode material for devices that harness chemical and electrochemical processes, such as electrocatalysts, energy storage and conversion, sensing and biosensing [3][4][5]. While the characteristic extended honeycomb lattice of graphene is absent throughout LIG structures, they usually possess numerous structural imperfections, such as pentagonal and heptagonal carbon rings and various functional groups, useful in the above-mentioned applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lasing LIG with complex geometry on flexible substrates and the possibility to transfer it onto stretchable and adhesive hydrogels, conformal to natural skin, make it appealing for wearable bioelectronics, e-skin and soft robotics [12]. However, there are challenges associated with LIGs, such as significant dependence of the produced LIGs on lasing parameters, utilized raw materials, such as the brand of PI foil, or even the environmental stability of the LIGs during storage [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…38,45−47 These new materials boast broad sources, environmental friendliness, and high biocompatibility, offering a viable path toward green and sustainable LIG electronics. 48,49 Despite the advantages, these materials often fall short as flexible supporting films due to their intrinsically poor mechanical and physicochemical characteristics and face limitations in preparing highly reliable and antiaging LIG devices. 50,51 For instance, extensively studied paper-based LIG devices are extremely vulnerable to high-temperature combustion, water infiltration, mechanical tearing, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This constraint underscores the persistent need for innovative carbon feedstocks in LIG electronics. Recent studies have revealed that natural renewable materials, along with their individual-component extracts or processed goods, can serve as carbon precursors for producing high-quality LIGs and advancing micronano devices, especially those rich in lignin or cellulose structures. ,− These new materials boast broad sources, environmental friendliness, and high biocompatibility, offering a viable path toward green and sustainable LIG electronics. , Despite the advantages, these materials often fall short as flexible supporting films due to their intrinsically poor mechanical and physicochemical characteristics and face limitations in preparing highly reliable and antiaging LIG devices. , For instance, extensively studied paper-based LIG devices are extremely vulnerable to high-temperature combustion, water infiltration, mechanical tearing, etc. − While methods like common reverse-mold peeling have been developed to transfer LIG to robust substrates for enhanced reliability, , the transfer process often damages the architectures of LIGs, significantly impacting the final device performance. Consequently, exploring innovative green precursors while ensuring the preparation of highly reliable devices proves to be a formidable challenge for LIG electronics, particularly for flexible on-chip MSCs featuring meticulously designed in-plane electrodes.…”
Section: Introductionmentioning
confidence: 99%